2021
DOI: 10.1093/noajnl/vdab125
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma as an age-related neurological disorder in adults

Abstract: Background Advanced age is a major risk factor for the development of many diseases including those affecting the central nervous system (CNS). Wild-type isocitrate dehydrogenase glioblastoma (IDH wt GBM) is the most common primary brain cancer and accounts for ≥90% of all adult GBM diagnoses. Patients with IDH wt GBM have a median age of diagnosis at 68-70 years of age and increasing age is associated with an increasingly worse prognosis for patients with this type of GBM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 91 publications
2
33
2
Order By: Relevance
“…In fact, the BS149 cell line generated from recurrent glioblastoma is more malignant than the other four glioblastoma cell lines (LN018, LN215, LN229, and LN319) and has higher mRNA levels of DPP4, ANPEP, and ENPEP ( Figure 2A ), further corroborating the potential oncogenic roles of ANPEP and ENPEP in GBM. Moreover, the levels of ANPEP and ENPEP were significantly upregulated with increasing age and peaked at 60–80 years old ( Figure S1A ), which agrees with the peak incidence of GBM between 70 and 79 years old ( 77 ). Kaplan–Meier survival curves and the Cox regression analysis demonstrated that high expression of ANPEP and ENPEP was associated with poor prognosis and that ENPEP was a negative predictor of survival.…”
Section: Discussionsupporting
confidence: 77%
“…In fact, the BS149 cell line generated from recurrent glioblastoma is more malignant than the other four glioblastoma cell lines (LN018, LN215, LN229, and LN319) and has higher mRNA levels of DPP4, ANPEP, and ENPEP ( Figure 2A ), further corroborating the potential oncogenic roles of ANPEP and ENPEP in GBM. Moreover, the levels of ANPEP and ENPEP were significantly upregulated with increasing age and peaked at 60–80 years old ( Figure S1A ), which agrees with the peak incidence of GBM between 70 and 79 years old ( 77 ). Kaplan–Meier survival curves and the Cox regression analysis demonstrated that high expression of ANPEP and ENPEP was associated with poor prognosis and that ENPEP was a negative predictor of survival.…”
Section: Discussionsupporting
confidence: 77%
“…For this reason, Kim defines GBM from a clinical and epidemiological point of view as a neurological disease characteristic of older men [ 11 ]. In addition, Ostrom also reports an average annual incidence of 3.99 per 100,000 capita for males and a significantly lower 2.52 per 100,000 capita for females in a similar age-dependent pattern to the current study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes for brain tumor patients are influenced by many factors, including disease growth rate and duration, tumor size, grade of malignancy, and patient age. Tumor location has a particularly important impact on outcomes [1][2][3][4][5][6][7]. Approximately 60% of brain tumors-especially gliomas-are sited in the cerebral hemispheres, over half of which are highly malignant glioblastomas [1,4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor location has a particularly important impact on outcomes [1][2][3][4][5][6][7]. Approximately 60% of brain tumors-especially gliomas-are sited in the cerebral hemispheres, over half of which are highly malignant glioblastomas [1,4,[6][7][8]. These can cause a constellation of symptoms depending on the affected lobe.…”
Section: Introductionmentioning
confidence: 99%